THE CONCEPT AND PREVALENCE OF HELICOBACTER PYLORI INFECTION - Khudaiberganova N.H; Alikulov I.T; Khatimbetov J.Sh; Narziev N.M. (Western European Studies, 2025)
Helicobacter pylori bacterium (HP), a etiopathogenetic agent of a number of “gastric”, including stomach cancer, and “extra -yielding” diseases, affects more than 50% of the planet’s population. The duration of the evolution of this microorganism in the human population is more than 100 thousand years. The modern epidemic process of the HR infection is characterized by three patterns:1) the nature of the infection of the population dependent on the age; 2) the slow process of spontaneous release of the population from infection; 3) re - infection of part of the recovered population. The equal these processes leads to a gradual decrease in the infection of the population in developed countries. In the countries of the developing world, there is a stable high infection and high incidence of diseases associated with HP.It is concluded that medical science and medical measures make an important contribution to the liberation of mankind from HP infection, but at the present stage the leading role in this case is played by the standard of living and public hygiene and the culture of the content of houses, nutrition and consumption of alcohol, service, and physical contacts between people.
Keywords: Helicobacter pylori; peptic ulcer; risk factors for infection